Edukasi Pariwisata Serta Profesi Bidang Usaha Perjalanan Wisata Bagi Siswa SMP Negeri 2 Kelapa Dua Tangerang - Yustisia Kristiana; Reagan Brian; Nova I. B. Sitoru; Stephanie T. Mulyono (LPPM UNIVERSITAS DIAN NUSWANTORO, 2021)
The introduction of tourism development at the Junior High School level is indispensable. This is because the workforce in the tourism industry is dominated by education graduates up to Junior High School. By providing knowledge about tourism from an early age, it is hoped that it can produce competent and competitive human resourcesThe partner of this activity is SMP Negeri 2 Kelapa Dua Tangerang. The purpose of this activity is to increase students' knowledge about tourism in Indonesia and profession in travel industry. The method is carried out in several stages starting with surveys, coordination with partners, preparation of materials, implementation, and evaluation. This activity was attended by participants as many as 50 students. The results of this activity can be declared successful. This can be seen from (1) the level of attendance of the participants (2) the level of understanding of the participants, and (3) the realization of cooperation. The implication of this activity is to increase students' knowledge about tourism and to understand the profession in the tourism travel industry.